Pathogen blocking in Wolbachia-infected Aedes aegypti is not affected by Zika and dengue virus co-infection. - Eric P Caragata; Marcele N Rocha; Thiago N Pereira; Simone B Mansur; Heverton L C Dutra; Luciano A Moreira (PLoS Neglected Tropical Diseases, 2019)
Background Wolbachia's ability to restrict arbovirus transmission makes it a promising tool to combat mosquito-transmitted diseases. Wolbachia-infected Aedes aegypti are currently being released in locations such as Brazil, which regularly experience concurrent outbreaks of different arboviruses. A. aegypti can become co-infected with, and transmit multiple arboviruses with one bite, which can complicate patient diagnosis and treatment. Methodology/principle findings Using experimental oral infection of A. aegypti and then RT-qPCR, we examined ZIKV/DENV-1 and ZIKV/DENV-3 co-infection in Wolbachia-infected A. aegypti and observed that Wolbachia-infected mosquitoes experienced lower prevalence of infection and viral load than wildtype mosquitoes, even with an extra infecting virus. Critically, ZIKV/DENV co-infection had no significant impact on Wolbachia's ability to reduce viral transmission. Wolbachia infection also strongly altered expression levels of key immune genes Defensin C and Transferrin 1, in a virus-dependent manner. Conclusions/significance Our results suggest that pathogen interference in Wolbachia-infected A. aegypti is not adversely affected by ZIKV/DENV co-infection, which suggests that Wolbachia-infected A. aegypti will likely prove suitable for controlling mosquito-borne diseases in environments with complex patterns of arbovirus transmission.